Biomarkers for prediction of skeletal disease progression in mucopolysaccharidosis type I. Issue 1 (8th December 2020) - Lund, Troy C.; Doherty, Terence M.; Eisengart, Julie B.; Freese, Rebecca L.; Rudser, Kyle D.; Fung, Ellen B.; Miller, Bradley S.; White, Klane K.; Orchard, Paul J.; Whitley, Chester B.; Polgreen, Lynda E.
Abstract: Background: Orthopedic disease progresses in mucopolysaccharidosis type I (MPS I), even with approved therapies and remains a major factor in persistent suffering and disability. Novel therapies and accurate predictors of response are needed. The primary objective of this study was to identify surrogate biomarkers of future change in orthopedic disease. Methods: As part of a 9‐year observational study of MPS I, range‐of‐motion (ROM), height, pelvic radiographs were measured annually. Biomarkers in year 1 were compared to healthy controls. Linear regression tested for associations of change in biomarkers over the first year with change in long‐term outcomes. Results: MPS I participants (N = 19) were age 5 to 16 years and on average 6.9 ± 2.9 years post treatment initiation. Healthy controls (N = 51) were age 9 to 17 years. Plasma IL‐1β, TNF‐α, osteocalcin, pyridinolines, and deoxypyridinolines were higher in MPS than controls. Within MPS, progression of hip dysplasia was present in 46% to 77%. A 1 pg/mL increase in IL‐6 was associated with −22°/year change in ROM (−28 to −15; P < .001), a 20 nmol/mmol creatinine/year increase in urine PYD was associated with a −0.024 Z‐score/year change in height Z‐score (−0.043 to −0.005; P = .016), and a 20 nmol/mmol creatinine/year increase in urine PYD was associated with a −2.0%/year change in hip dysplasia measured by Reimers migration index (−3.8 to −0.1; P = .037). Conclusions: Inflammatory cytokines are high in MPS I. IL‐6 and PYD were associated with progression in joint contracture, short stature, and hip dysplasia over time. Once validated, these biomarkers may prove useful for predicting response to treatment of skeletal disease in MPS I.